Latent autoimmune diabetes in youth shows greater autoimmunity than latent autoimmune diabetes in adults: Evidence from a nationwide, multicenter, cross‐sectional study. Issue 5 (17th May 2022) - Cheng, Jin; Tang, Xiaohan; Yan, Xiang; Huang, Gan; Luo, Shuoming; Zhou, Zhiguang; Li, Xia
Abstract: Aim: To investigate the prevalence and clinical features of latent autoimmune diabetes in youth (LADY) diagnosed between 15 and 29 years old as a component of an age‐related autoimmune diabetes spectrum. Research Design and Methods: This nationwide, multicenter, cross‐sectional study continuously included 19, 100 newly diagnosed diabetes patients over 15 years old across China. LADY patients were screened from 1803 subjects aged between 15 and 29 years old, with the type 2 diabetes (T2D) phenotype and positive autoantibodies against glutamic acid decarboxylase (GADA), insulinoma‐associated‐2 (IA‐2A) or zinc transporter‐8 (ZnT8A). The clinical features of LADY, including metabolic status, β‐cell function and insulin resistance, were investigated and compared with those of latent autoimmune diabetes in adults (LADA) identified from 17, 297 other subjects over 30 years old. The age‐related characteristics of the latent autoimmune diabetes spectrum were explored. Results: A total of 135 subjects were diagnosed as LADY, accounting for 9.0% of the T2D phenotypic youth. Compared with autoantibody‐negative T2D patients, LADY patients had fewer metabolic syndrome, less insulin resistance and poorer β‐cell function, which were closely related to their autoantibody status (all p  < 0.05). After stratifying LADA according to age, the GADA titer decreased across the LADY, "Y‐LADA" (young LADA, onset age < 60 years old) and "E‐LADA" (elderly LADA, onset age ≥ 60 years old) groups, while the prevalence of metabolic syndrome and level of β‐cell function increased (all p  < 0.05). Conclusions: A high prevalence of LADY exists in youth with T2D phenotype. Latent autoimmune diabetes forms a continuous age‐related spectrum from LADY to LADA, in which LADY shows greater autoimmunity.